Evaluation of balance using cervical vestibular evoked myogenic potentials in blind individuals - OYSU, ÇAĞATAY (My University, 2022)
Objective: Our purpose in this study is to investigate whether blindness affects vestibulocollic reflex. Material and Methods: This is a prospective case control series. We recorded cervical vestibular evoked myogenic potential in 29 blind and 26 sighted subjects, and compared the latency and amplitude values. Results: Twenty one of the blind subjects were male and 8 were female, the average of age was 41.72±11.83 years. Nineteen of the sighted subjects were male and 7 were female, the average of age was 40.64±9.11 years. The average P13 latency value was 16.97±2.12 ms in the blind group and 15.40±0.88 ms in the sighted group. The average P13 latency value was longer in the blind group (p<0.005). In the blind subjects, the average N23 latency was 24.92±2.77 ms. In the sighted subjects, the average N23 latency was 23.73±0.85 ms. The average N23 latency value was longer in the blind group (p<0.005). The mean P13-N23 interpeak amplitude was 2.76±2.92 µV in the blind group. In the sighted group, it was 2.38±0.33 µV. There were not statistically significant differences between the mean P13-N23 interpeak amplitudes (p>0.005). Conclusion: We determined that the P13 latency values and N23 latency values were longer in the blind group. Our study has shown that cervical vestibular evoked myogenic potential responses in the blind individuals are different from the sighted individuals.

Amaç: Bu çalışmadaki amacımız, körlüğün vestibülokolik refleks yanıtları üzerindeki etkisini araştırmaktır. Gereç ve Yöntemler: Bu çalışma, prospektif vaka kontrol çalışmasıdır. Çalışmamızda, 29 görme engelli ve 26 normal görmeye sahip bireyde servikal vestibüler uyarılmış miyojenik potansiyeli kaydettik, latans ve amplitüd değerlerini karşılaştırdık. Bulgular: Görme engelli bireylerin 21’i erkek, 8’i kadın olup yaş ortalaması 41,72±11,83 yıl idi. Görmesi normal olanların 19’u erkek, 7’si kadın olup; yaş ortalaması 40,64±9,11 yıl idi. Ortalama P13 latans değeri, görme engelli grupta 16,97±2,12 ms; görmesi normal olan grupta ise 15,40±0,88 ms idi. Görme engelli grupta ortalama P13 latans değeri, görmesi normal olan gruba göre daha uzamış saptandı (p<0,005). Görme engelli grupta ortalama N23 latans değeri 24,92±2,77 ms; görmesi normal olan grupta ise ortalama N23 latansı 23,73±0,85 ms idi. Görme engelli grupta ortalama N23 latans değeri, görmesi normal olan gruba göre daha uzamış olarak saptandı (p<0,005). Görme engelli grupta ortalama P13-N23 interpeak amplitüdü 2,76±2,92 µV; görmesi normal olan grupta ise 2,38±0,33 µV idi. Ortalama P13-N23 interpeak amplitüd değerleri karşılaştırıldığında, görme engelli olan grup ile görmesi normal olan grup arasında istatistiksel olarak anlamlı fark saptanmadı (p>0,005). Sonuç: Görme engelli grupta P13 ve N23 latans değerlerinin daha uzun olduğunu belirledik. Çalışmamızda, görme engellilerde servikal vestibüler uyarılmış miyojenik potansiyel yanıtlarının görmesi, normal bireylerden farklı olduğunu ortaya konmuştur
Keywords: Vestibular evoked myogenic potentials; blindness; posture balance: Vestibüler uyarılı miyojenik potansiyeller; körlük; postür dengesi